Quantitative real time PCR analysis of apoptosis-related gene expression in leukemias in ukrainian patients - Savli, H.; Gluzman, D.F.; Sunnetci, D.; Zavelevich, M.P.; Sklyarenko, L.M.; Nadgornaya, V.A.; Koval, S.V. (Experimental Oncology, 2011)
Background: The complete medical consequences of the long-term exposure of population to ionizing radiation in post-Chernobyl period are still a controversial issue. The molecular biological analysis of malignant diseases of hematopoietic and lymphoid tissues in contaminated territories requires the precise diagnosis based on criteria of novel classifications. Aim: To analyze the relative gene expression of six apoptosis-related genes in different types of tumors of hematopoietic and lymphoid tissues in patients living in areas of Ukraine contaminated with radionuclides in post-Chernobyl period. Material and methods: The samples of the peripheral blood and bone marrow of 189 Ukrainian leukemia patients and 16 patients with reactive lymphocytosis were analyzed morphologically and immunocytochemically for precise delineation of the main forms and cytological variants of hematological malignancies according to new WHO classification. Expression of six apoptosis-related genes was analyzed in the individual samples of 9 different groups of malignant diseases of hematopoietic and lymphoid tissues and one group of patients with reactive lymphocytosis by quantitative RT-PCR. Expression of genes was assessed relative to that in control group of healthy donors. Results: Up-regulation of six analyzed apoptosis-related genes is observed in all groups of leukemia. In most groups of leukemia being analyzed, BCL-2 up-regulation level is superior to that of BAX. Prominent MYC up-regulation is observed in B-lymphoblastic leukemia/lymphoma, non-Hodgkin’s lymphoma, and T-lymphoblastic leukemia/lymphoma groups. In myelodysplastic/myeloproliferative neoplasms, the striking up-regulation of Fas-1 and P38MAPK is evident. Practically all the groups of leukemia are characterized by stable high ratios of P53 up-regulation. Conclusion: In Ukrainian patients, up-regulation of six analyzed apoptosis-related genes is observed practically in all types of malignant diseases of hematopoietic and lymphoid tissues under study. Microarray-based analysis of these samples would be of great importance in terms of elucidating genomic interactions in leukemias and their possible association with ionizing radiation.